Estimando o valor ambiental do Parque Nacional do Iguaçu: Uma aplicaç\~ao do método de custo de viagem - Ramon Arigoni Ortiz; Ronaldo Serôa da Motta; Claudio Ferraz (Instituto de Pesquisa Econômica Aplicada (IPEA), 2001)
– The Travel Cost Method (TCM) estimates recreational use values through the analysis of travel expenditures incurred by consumers to enjoy recreational activities. The multiple destination or multipurpose problems arise when tourists either visit other attractions or have any other purpose in the same trip. Since this issue is not tractable with the basic approach of TCM, we apply distinct approaches to account for that. Our results indicate that the recreational use value of the Iguaçu Falls National Park may vary within the range of US 12 to 34 millions.
Keywords: 330; Umweltbewertung; Naturschutzgebiet; Theorie; Brasilien